Hubungan antara Komunikasi Interpersonal dengan Kinerja Guru SMK Swasta di Kecamatan Bogor Utara Kota Bogor - Wisnu Diputra; Neti Karnati; Matin Matin (Program Studi Manajemen Pendidikan, 2017)
This study aims to know there is a relationship between headmastersinterpersonal communication with teachers performance at Vocational High SchoolNorth Bogor District, Bogor City. This research use quantitative with two variables therein, namely: (X) interpersonal communication as independent variable and (Y) teachersperformance as the dependent variable. The method used is survey method with theresults of the analysis of correlational studies. The population in this study are teachersat vocational high school in North Bogor District, Bogor City, there are 580 teachers.Samples were taken by using simple random sampling technique. The technique is basedon the sample size used in this study as many as 85 teachers. Data collection for thevariable (X) interpersonal communication and variable (Y) teachers performance using aquestionnaire. Hypothesis testing is done by using product moment correlation formulaand getting the correlation coefficient (r) value = 0,58892 and based on the results ofhypothesis testing by using t-test obtained t for 6,639 Ëƒ 1,671 t-tables. By this research,we get a positive relation between interpersonal communication with teachersperformance at Vocational High School North Bogor District, Bogor City.